Bringing the British back in: Sephardim, Ashkenazi anti-Zionist Orthodox and the policy of Jewish unity. Issue 2 (3rd March 2016) - Sontheimer, Tim
ABSTRACT: This article analyses the British role in establishing and maintaining a Jewish–Arab demarcation line by means of a policy of Jewish unity and by enabling Ashkenazi Zionist control of the Yishuv. In the first part, it analyses British policy towards the local Sephardi as well as the local Ashkenazi anti-Zionist Orthodox communities, both of which for different reasons did not neatly fit into the Jewish/Zionist–Arab binary. I argue that the British followed a policy of Jewish unity at the inception of the Mandate which they upheld repeatedly against Ashkenazi anti-Zionist Orthodox efforts and which by 1936 had created a truism enforcing a binary understanding of the conflict. In the second part, this article analyses the ways in which these communities presented themselves vis-à-vis the British. I argue that despite different strategies of maximizing their influence, both communities foundered on the existing power configurations.